Delayed Radiological Changes in a Patient With Inhaled Foreign Bodies: A Case Report - Anwar, Ali; Naqvi, Mazhar Ali; Nazir, Humaira; Tahir, Muhammad Mubashir; Khan, Agha Hashim Raza; Ahmad, Daler (Biological and Clinical Sciences Research Journal, 2025)
Foreign body aspiration (FBA) and aspiration pneumonia are uncommon but potentially lethal events in adults. Airway obstruction by aspirated food or other material can lead to hypoxaemia and delayed radiological changes. International reporting standards emphasise structured, transparent case reports to improve completeness and utility. Case Presentation: A 55‑year‑old man with a history of recurrent strokes and dementia developed sudden dyspnoea and altered consciousness during a meal. Initial vital signs showed oxygen saturation of 77% on room air, blood pressure 190/100 mm Hg, and a Glasgow Coma Scale score of 5/15. Following resuscitation and high‑flow oxygen, his oxygen saturation improved. The first chest radiograph was normal. Ten hours later, the radiograph remained unremarkable. Eighteen hours after presentation, a third radiograph demonstrated right middle‑ and lower‑lobe atelectasis. Emergency bronchoscopy under local anaesthesia revealed obstructing food particles ("roti") in the right lower lobar bronchus, which were removed. Post‑procedure imaging showed re‑expansion of the collapsed lobes. The patient was observed for 30 hours, regained baseline neurological status, and was discharged with outpatient follow‑up. Conclusion: This case highlights that initial chest radiographs may be normal following aspiration events. Delayed radiological changes warrant repeat imaging when clinical suspicion of FBA persists. Prompt bronchoscopic removal of the foreign body is critical for preventing complications, consistent with current recommendations(2). Adhering to established reporting guidelines enhances the value of case reports for clinicians and researchers.